Effects of Refined Sugar on Some Endocrine Glands Functions in Mice - Rana Jaber Tarish Al-Baghdadi (Journal of Global Pharma Technology, 2018)
Endocrine and nervous systems regulate blood glucose level in our bodies, but the reciprocal action yet to be addressed. To address this question, we employed the current study that included 24 mice of both sexes that were divided into control group that consumed standard mouse diet, a group that consumed high refined sugar diet (HS), a group that consumed high refined sugar and Vaccinium corymbosum L fruit powder diet (HSP). The study lasted for 3 months. The measured parameters included body weight gain, pancreas weight, glucose tolerance test and the leptin and thyroid hormone receptor gene expression. The results showed that the HS mice showed the highest body weight gain, pancreas weight, glucose blood level, and leptin gene expression. Most of those parameters went back to normal in the HSP group. In conclusion, the study reveals the deleterious effect of consuming refined sugar diet on the health and more specifically on the endocrine system response. The study shows that consuming refined sugar diet might be a precursor to initiate type 2 diabetes as a result of chronic high glucose level and insulin resistance. It also works as predisposing factor to develop obesity as the result shows high body weight gain and high leptin level indicating that the body develops leptin resistance as well. Keywords: leptin, Thyroid hormone, Refined sugar, Vaccinium corymbosum, Glucose.